KEHIDUPAN BERAGAMA MASYARAKAT NELAYAN DI JAWA TENGAH DAN JAWA TIMUR - Darno . (Analisa: Journal of Social Science and Religion, 2008)
Many factors, such as season fluctuations, limited humanresources, limited capital, trading networks, belief norms which livedamong the community, having not side jobs, influence daily economicactivities of Fisherman community in Central and West Java. Hence,when there come time of 'famine.fisherman have not any contributions to economic earnings for supporting daily needs. The only thingleft is selling anything they have to meet their daily needs. Thispoverty has always been a picture of daily life of the fisherman inCentral and West Java. Their religious lives, with most of them are Muslim, worshipAllah through sholat in shore at the mosque or at home. While theyare at the sea, they will anchor their boat facing kiblat and do sholaton it. They still believe in Nyi Rora Kidul for those fishermen livedin south coast and Nabi Khidir for those lived in north coast as thesea master.